Implementasi Model Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fikih - Syihabuddin, Ahmad Ali; Nursyamsiyah, Siti; Putra, Dhian Wahana (Jurnal Pendidikan Islam, 2023)
The purpose of this research is: (1) to examine the implementation of Islamic jurisprudence education through a problem-based learning (PBL) approach, (2) to determine whether the utilization of the PBL teaching model leads to an improvement in students' learning achievement, and (3) to explain the results of jurisprudence learning when using the PBL model. The research methodology used in this study is the classroom action research (CAR) method. CAR serves as a mechanism for addressing potential challenges in the educational environment. The procedure consists of four distinct phases, namely planning, implementation, observation, and reflection. The iterative process of these four phases is characterized by a consistent sequence of steps and is focused on discussion-based learning aimed at honing problem-solving skills through the PBL model. The research results indicate a significant improvement in student learning outcomes through the implementation of the PBL model. The observed improvement is evident through the cycles that were carried out. In cycle I, the average score for the pretest was 29.26, and the average score for the posttest was 73.68. In cycle II, the average pretest score was 47.68, and the average posttest score was 86. The use of the PBL model in jurisprudence subjects has been observed to yield optimal learning outcomes, as evidenced by an achievement score of 86.84%.